HUBUNGAN KUALITAS TIDUR DENGAN 5 INDIKATOR SINDROMA METABOLIK PADA PERAWAT DI RUMAH SAKIT UMUM PUSAT HAJI ADAM MALIK MEDAN - simon simon; Ida Yustina; Fazidah Aguslina Siregar (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
ABSTRACTHigh death rate caused by non-transmitted diseases in the world is begun with metabolic syndrome in human beings such the increase in IMT (Body Mass Index) to be obesity, the increase in blood pressure to be hypertension, the increase in blood glucose to be diabetes mellitus, and abnormality of triglycerides, and  HDL cholesterol. Many factors which trigger the indicator abnormality, and of them is bad sleep quality. The research used cross sectional design by analyzing the correlation between sleep quality and 5 metabolic syndrome indicator in female nurses in the operation room of Adam Malik Medan hospital. Sleep quality was measured by using questionnaire of Pittsburg Sleep Quality Index (PSQI), body height and weight were measured to get IMT value, blood pressure was measured by using tensimeter, blood glucose and blood lipid were measured by getting the respondent’s vena blood samples. The data were processed and analysis with independent t-test.The result with independent t-test showed that there was significant difference in IMT (sig=0,003), systolic blood pressure (sig=0,028), and fasting blood glucose content (sig=0,00). However, there was no significant difference in trigliyceride content (sig=0,519), HDL cholesterol content (sig=0,300),). The conclusion was that sleep quality was correlated with three metabolic syndrome indicators: IMT, blood pressure, and blood glucose content, but there was no correlation with trigliyceride and HDL cholesterol.Keywords: Sleep Quality, Metabolic Syndrome , T-Test,